2013
DOI: 10.1182/blood-2013-02-481887
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant HPA-1a antibody therapy for treatment of fetomaternal alloimmune thrombocytopenia: proof of principle in human volunteers

Abstract: Key Points• Recombinant antibody B2G1Dnab protects platelets from destruction by anti-HPA-1a in the circulation of HPA-1a1b human volunteers.• B2G1Dnab is a potential therapeutic agent for antenatal treatment of fetomaternal alloimmune thrombocytopenia due to HPA-1a antibodies.Fetomaternal alloimmune thrombocytopenia, caused by the maternal generation of antibodies against fetal human platelet antigen-1a (HPA-1a), can result in intracranial hemorrhage and intrauterine death. We have developed a therapeutic hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 40 publications
(33 reference statements)
1
38
0
7
Order By: Relevance
“…In support of the feasibility of Ab prophylaxis with HPA-1a-specific mAbs, we have demonstrated in vitro that both IgG1 and IgG3 subclasses of recombinantly expressed mAb 26.4 are able to induce phagocytosis of HPA-1a + platelets. Also, rapid clearance of autologous HPA-1ab platelets that were sensitized ex vivo with the HPA-1a-specific human mAb B2G1 was demonstrated in a recent study (35). Furthermore, our demonstration that mAb 26.4 can efficiently block maternal polyclonal HPA-1a-specific IgG from various donors from binding platelets suggests that the mAb could also interfere with binding to receptors on HPA-1a-specific B cell clones in women susceptible to immunization.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In support of the feasibility of Ab prophylaxis with HPA-1a-specific mAbs, we have demonstrated in vitro that both IgG1 and IgG3 subclasses of recombinantly expressed mAb 26.4 are able to induce phagocytosis of HPA-1a + platelets. Also, rapid clearance of autologous HPA-1ab platelets that were sensitized ex vivo with the HPA-1a-specific human mAb B2G1 was demonstrated in a recent study (35). Furthermore, our demonstration that mAb 26.4 can efficiently block maternal polyclonal HPA-1a-specific IgG from various donors from binding platelets suggests that the mAb could also interfere with binding to receptors on HPA-1a-specific B cell clones in women susceptible to immunization.…”
Section: Discussionsupporting
confidence: 60%
“…This may be achieved by protecting fetal tissues and platelets from potentially damaging anti-HPA-1a Abs with Abs that compete for binding to HPA-1a but lack the ability to activate immune effector functions. This is not a new concept and has been proved to function in principle with HPA-1a-specific mAbs both in a murine model and in human volunteers (35,36). The stable binding of mAb 26.4 to both platelet-derived and trophoblast-derived HPA1a, as demonstrated in this study, could be an additional advantage for therapeutic purposes because anti-HPA-1a Abs have been reported to have possible negative effects on fetal growth, in addition to causing thrombocytopenia in the fetus (5,37).…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐FcγR immunoglobulins may have the capacity to reduce PLT destruction . Another approach consists of preventing PLT destruction using recombinant HPA‐1a–specific antibodies with abrogated Fcγ receptor binding . These antibodies have the capacity to saturate available HPA‐1a–binding sites from fetal PLTs without activating FcγR signaling.…”
Section: What Might the Future Hold?mentioning
confidence: 99%
“…For the future, a recent proof-of-principle study has shown that a recombinant anti-HPA-1 antibody can, in vivo , block platelet destruction by immune HPA-1 IgG antibodies [33]. …”
Section: Immune Thrombocytopenias (Nait/itp)mentioning
confidence: 99%